Doug rules - Krulik, Nancy E.; Donnelly, Brian; Curanaj, Tony.; Jinkins, Jim. (New York : Disney Press, 1999)
When Doug wins a prize to become principal of Beebe Bluff Middle School, he outlaws all rules.
"Jumbo pictures."
"Disney chapters"--Cover.
007-009.
Accelerated Reader AR
Keywords: Schools -- Fiction